1989
DOI: 10.1055/s-0038-1646627
|View full text |Cite
|
Sign up to set email alerts
|

Plasma D Dimer: A Useful Marker of Fibrin Breakdown in Renal Failure

Abstract: SummaryD dimer and other large fragments produced during the breakdown of crosslinked fibrin may be measured by enzyme immunoassay using monoclonal antibodies. In 91 patients with renal disease and varying degrees of renal dysfunction, plasma D dimer showed no correlation with renal function, whereas FgE antigen, a fibrinogen derivative which is known to be cleared in part by the kidney, showed a significant negative correlation with creatinine clearance. Plasma concentrations of D dimer were, however, increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 6 publications
3
28
0
1
Order By: Relevance
“…It has been recently reported that patients with liver disease have elevated plasma fibrin degradation prod ucts whereas fibrinogenolysis products are normal [12]. On the other hand, Gordge et al [13] have observed high levels of D dimer in patients with chronic renal failure using a highly sensitive ELISA method. It appears to be the result of coagulation activation rather than a decrease in D dimer elimination.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that patients with liver disease have elevated plasma fibrin degradation prod ucts whereas fibrinogenolysis products are normal [12]. On the other hand, Gordge et al [13] have observed high levels of D dimer in patients with chronic renal failure using a highly sensitive ELISA method. It appears to be the result of coagulation activation rather than a decrease in D dimer elimination.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Other studies have identified renal dysfunction as a state of activated coagulation due to the elevated D-dimer levels, which are not cleared by the kidney. 20,21 Although fibrinogen levels are thought to be primarily determined by fibrinogen synthesis, Lane and colleagues 22 found the metabolism and elimination of fibrinogen to be decreased in renal insufficiency and ESRD. The role of the kidney in the elimination of these biomarkers has not been established, nor is it known whether mild to moderate renal insufficiency has an impact on their clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller studies have found decreased renal function is correlated with fibrinogen, IL-6, and D-dimer, but they had inadequate power to determine the independence of these associations or the effect of prevalent cardiovascular disease. 20,27 Studies in persons with insulin resistance and diabetes found microalbuminuria was associated with increased fibrinogen levels. 28 Although our findings in conjunction with prior studies seem to demonstrate that inflammatory and procoagulant biomarkers are elevated in persons with renal insufficiency, we cannot determine the direction of the association because of the cross-sectional design of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid bedside tests are available in human medicine and are an accurate and reliable means to either rule out thromboembolic disease or lead the clinician to order advanced imaging studies . D‐dimers have been shown to be increased in numerous conditions in people including deep vein thrombosis, surgery, trauma, pregnancy, smoking, disseminated intravascular coagulation (DIC), asthma, pneumonia, pulmonary hypertension, neoplasia, critical illness, chronic renal failure, and heart failure . It is the state of increased clot production and breakdown that leads to the increase of D‐dimers in all of these conditions .…”
Section: Thromboembolic Diseasementioning
confidence: 99%